Agility Barriers Analysis in the Malaysian Palm Oil Industry - Nitty Hirawaty Kamarulzaman; Aroop Mukherjee; Mad Nasir Shamsudin; Ismail Abd Latif (International Journal of Supply Chain Management, 2015)
In a volatile global marketplace, the implementation of agility is viewed as fundamental key strategic consideration for the survival. In order to achieve competitive advantage and ready to adapt to potential changes, implementation of agility in the palm oil industry is considered to be major challenges due to different obstacles. However, these obstacles can be overcome with the implementation of a proper strategic decision as well as high commitments from all management levels to make changes in day-to-day activities. The main purpose of this study is to investigate the obstacles in implementing agility in the Malaysian Palm Oil Industry (MPOI). The survey was conducted in Peninsular Malaysia with 69 oil palm plantation estates. The mean ranking analysis was used to ascertain the rank of various agile statements for its implementation in the organization. The study revealed that strict budget was the biggest obstacle along with laid back attitude of the employee for implementing agility in the organization. The outcomes of this research provide an invaluable information to all strategic decision makers who desire their organizations to be an agile and be competitive in the market and to sustain in todays competitive market as well as to maintain its dominant position in the world market.